Flow patterns in the ductus arteriosus during open fetal myelomeningocele repair1. (18th March 2015) - Howley, Lisa; Wood, Cristina; Patel, Sonali S.; Zaretsky, Michael V.; Crombleholme, Timothy; Cuneo, Bettina
Abstract Objective The objective of this study is to perform a longitudinal evaluation of blood flow patterns in the ductus arteriosus (DA) during the perioperative period in fetal myelomeningocele (MMC) surgical patients. Method Serial fetal echocardiograms were reviewed in 10 MMC cases where mothers received indomethacin and intravenous and inhaled anesthesia. One‐way analysis of variance was utilized to evaluate for differences in peak systolic velocity, end‐diastolic velocity (EDV), time‐averaged mean velocity (TAMV), and Pulsatility Index (PI) throughout the monitoring period. Regression analysis was performed to evaluate the relationship between PI and maternal hemodynamics and medications. Results The DA TAMV and EDV increased between baseline and inhaled anesthesia and decreased between inhaled anesthesia and postoperative day 2. PI decreased to a nadir during inhaled anesthesia and then increased through postoperative day 2. Three distinct ductal flow patterns, characterizing degree of ductal constriction, were observed. Two fetuses exhibited a severely constricted ductal flow pattern with concurrent moderate tricuspid insufficiency and right ventricular dysfunction during inhaled anesthesia. Conclusion Abnormal DA flow patterns culminating in significant DA constriction occurred during fetal MMC repair. Limiting maternal exposure to indomethacin, supplemental oxygen, and inhaled anesthesia may reduce the incidence and severity of DA constriction and perhaps reduce fetal cardiac dysfunction during open fetal surgery. © 2015 John Wiley & Sons, Ltd.